(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
For decades the Rule of Law has been emphasized as a core constitutional value common to all Member States of the European Union, although its substantial content was not precisely determined enough in the European context. Moreover it was defined as a multilayered value that encompasses other values such as democracy and fundamental rights, and it was underlined as one of the most important conditionality criteria for the EU enlargement policy. The ongoing crises of EU values, and more precisely the Rule of Law crisis, appeared long before, but reemerged fiercely with the creation of the “illiberal state“ concept in Hungary and then in Poland. The EU has implicitly and more successfully, through the work of its institutions tried to compensate for the inadequate and a “a little too late“ reaction, as well as for the lack of monitoring in the previous enlargement circles. The aim of this article is to show how, the rule of Law was stressed as a leading value shaping democratic constitutions and national, as well as supranational, legal systems. It is important to demonstrate that the Rule of Law is not only “coined” for the EU or Council of Europe purposes, but that it is firstly a value that is in the core of each constitutional tradition of a sovereign state. Therefore, in order to be promoted as common and set as a strong and rigid condition for future members, it should be, pro futuro, analyzed, understood and endorsed by EU institutions on each level. Finally, we take Western Balkan countries as an example where the Rule of Law is defined as a value but also as a core basis of the Negotiation Chapters 23 and 24, determined in a more thorough and precise way than in the EU and among its Member States, where, we could agree, it should have been in the first place. We point out to the need of getting closer to its uniform understanding in and outside of the EU and therefore to the need to create a continuous and stable Rule of Law concept both substantially and formally.